Microstructural changes in LMD p Ti 6Al 4V: influence of cooling rates during heat treatment - Subramanian, Sachin (My University, 2021)
Laser Metal Deposition (LMD) is an additive manufacturing technique being developed for several aerospace applications including the repair of aerospace engine components. Mechanical and microstructural properties of LMD Ti-6Al-4V vary from those obtained from conventionally processed routes, with the main influences being the process parameters and post processing heat treatment parameters such as temperature, holding time and cooling rate. This thesis work aimed at understanding the effect of varying the cooling rates during heat treatment on the microstructure of LMD (powder) Ti-6Al-4V. Local heat treatments were performed, and the resulting microstructures were analysed using Light Optical Microscope (LOM), Scanning Electron Microscope (SEM) and Hardness testing. In order to understand the influence of cooling rates on microstructural changes, key features such as alpha lath thickness, alpha-phase fraction, alpha-case formation and beta grain size were measured and characterized using appropriate image analysis software. The volume fraction of phases after heat treatments were simulated using simulation tools such as ThermoCalc and JMatPro, and a comparison was made between simulation and experimental results. Cooling rates during heat treatments were found to have no influence on the beta grain size and alpha-case thickness and less influence on the build hardness. Influence of cooling rates on alpha lath thickness and alpha-phase fraction was higher for heat treatments at temperatures close to beta-transus, with an increase in cooling rate leading to decreases in alpha-lath thickness and alpha-phase fraction. Simulation tools predicted trends of cooling rate influence on alpha-phase fraction similar to those experimentally observed but gaps were found between the two in the exact simulated and measured values.
Keywords: Titanium alloys; Ti-6Al-4V; Additive Manufacturing; Laser Metal Deposition; heat treatment; cooling rate; phase transformations; microstructure; hardness; alpha case; alpha phase; beta phase; beta grain size; alpha lath; JMatPro; ThermoCalc